Agronomic Performance and Productivity of Plant-Cane Sugarcane Under The Application of Various Dosage of Biofertilizer and Inorganic Fertilizer - Arinta Rury Puspitasari; Diana Ariyani; Rivandi Pranandita Putra (Pusat Penelitian Perkebunan Gula Indonesia, 2022)
Fertilization is one of the essential interventions in sugarcane cultivation. This research aimed to investigate solid biofertilizer (BF) effectiveness in various doses and combination with inorganic fertilizer (IF) on sugarcane agronomic performance and productivity so that the best dose combination of the two types of fertilizer on sugarcane can be observed. The field experiment was executed in the pattern-B sugarcane planting season/rainy season (October 2020) until the milled sugarcane harvest age at Afdeling Kaliputih, Kendenglembu, PT Perkebunan Nusantara XII, Banyuwangi, East Java, Indonesia. The experiment was performed with a randomized block design with three replicates. The treatment was a combination of doses of BF and IF, i.e., 1) without any fertilization; 2) 0% IF + 500 kg ha-1 BF; 3) 0% IF + 1,000 kg ha-1 BF; 4) 100% IF + 0 kg ha-1 BF; 5) 75% IF + 1,000 kg ha-1 BF; 6) 75% IF + 500 kg ha-1 BF; 7) 50% IF + 1,000 kg ha-1 BF; 8) 50% IF + 500 kg ha-1 BF; 9) 25% IF + 1,000 kg ha-1 BF; and 10) 25% IF + 500 kg ha-1 BF. Observed parameters were: 1) Seed germination (SG) percentage at 1 month after planting (MAP); 2) the number of stalks and tillers/clumps at 3 and 6 MAP; 3) Stalk height at 3, 6, and 11 MAP; 4) Stalk diameter at 6 and 11 MAP; 5) Sugarcane productivity, commercial cane sugar (CCS), and sugar crystal productivity at 12 MAP; and 6) Relative Agronomic Effectiveness (RAE). Results showed no significant difference among all the treatments in sugarcane SG percentage. Applying mixed BF and IF did not significantly affect the number of tiller/clumps, the number of stalks, stalk height, and stalk diameter of sugarcane at 6 and 11 MAP compared to the treatments of 100% IF. Among all the treatments, the highest sugarcane productivity, commercial cane sugar, and sugar crystal productivity were at the treatment 25% IF + 1,000 kg BF (135 ton ha-1), 50% IF + 500 kg BF (9.23%), and 75% IF + 500 kg BF (11.8 ton ha-1), respectively.